Strategi Pengembangan UMKM Dengan Ide Kreatif Melalui Program Kuliah Kerja Nyata Di Kelurahan Kolo - M.Rony Muhazir; Siska Andriani; Sholichatun Nisa; Fitrianingsih Fitrianingsih; Febi Febriyanti; Aris Munandar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The Real Work Lecture (Kuliah Kerja Nyata or KKN) at STIE Bima is a community empowerment activity carried out by students and Field Supervisors (DPL). This KKN program at STIE Bima took place from August 18 to October 18, 2023, in the Kolo Sub-District. It is undeniable that the Kolo Sub-District has natural potential that needs to be developed through tourism and marine resources by promoting Micro, Small, and Medium Enterprises (MSMEs) and creative industries to be more innovative. The method used in the implementation of the KKN at STIE Bima is through participatory approaches and community involvement in interactions and data collection with MSME actors at the Kolo Sub-District Office. The results obtained from this KKN program include the enhancement of the local community's knowledge in Kolo Sub-District in improving MSMEs and creative industries, thus creating new job opportunities for the community through the application of digital marketing and providing local tourism needs to attract both domestic and international tourists.